Abortion in Judaism - Schiff, Daniel, Dr. (Cambridge, UK ; New York : Cambridge University Press, 2002)
Abortion in Judaism presents a complete Jewish legal history of abortion from the earliest relevant biblical references through the end of the twentieth century. For the first time, almost every Jewish text relevant to the abortion issue is explored, providing important insights into the development of Jewish ethical principles.
The conundrum takes shape: foundational verses -- Evaluating life: Rabbinic perspectives on fetal standing -- Divining a prohibition: the positions of the Rishonim and Acharonim -- No clear consensus: the sages of a rising modernity -- The struggle returns: Jewish views begin to take form -- Confronting a new reality: legislation for a Jewish state -- A Halakhic challenge: discerning Jewish abortion principles.
Includes bibliographical references (pages 275-284) and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Abortion (Jewish law); Avortement -- Droit juif; RELIGION -- Judaism -- Theology; Abortion (Jewish law); Schwangerschaftsabbruch; Halacha; Judentum; Electronic books